Synthesis of Unzipping Polyester and a Study of its Photochemistry - Joo, Wontae; Wang, Wade; Mesch, Ryan; Matsuzawa, Kensuke; Liu, Di; Willson, C. Grant (Journal of the American Chemical Society, 2019)
Preparation of an unzipping polyester is reported. The monomer was prepared from benzoic acid in a four-step sequence. Step growth polymerization of the monomer provides the target polymer. Efficient depolymerization upon irradiation at 254 nm was confirmed with a quantum yield of >0.8. The photolysis mechanism was investigated, and the results of radical trapping experiments are consistent with an initial Norrish type I like homolysis followed by a radical mediated depropagation reaction driven by aromatization.